The fetish regarding the professional team in social care work - Bezerra, Waldez Cavalcante; Trindade, Rosa Lúcia Prédes (Argumentum, 2024)
Social care services are spaces for the work of distinct professionals who are not always clear about their specificities within team work. This research analyses the lack of differentiation of attributes and competencies in professional work in social care. Documentary and field research was carried out, fifteen workers from four social care facilities were interviewed, plus the four facility coordinators, giving nineteen participants in total. It concludes that the lack of differentiation of attributes is mediated by vectors external to the professions. This not only feeds a fetish regarding teamwork, supported by the expressions of interdisciplinarity, but also establishes forms of work organisation that become functional to the precarious logic of social services operating with reduced teams.